Do you really want to hurt me? The impact of contextual factors on the moderating role of dark leadership in the relationships between learning climate facilitation, employability and turnover intention in the Netherlands and China - Habets, Omar; Peters, Pascale; Van der Heijden, Beatrice; Stoffers, Jol; Blomme, Robert; Liao, Shudi (Frontiers in Psychology, 2023)
Introduction Both the Dutch and Chinese labor markets experience severe shortages of skilled personnel and high turnover rates, being distressing socio-economic factors. At the same time, large cross-cultural studies indicate that these national contexts are highly different from a socio-cultural perspective. When considering issues on employee development and retainment, the public debate opens for negative attributes as dark leadership, wondering if employees accept to be hurt. This study contributes to the employability research and, moreover, it contributes to the call for the ability to contextualize theories and to the convergence/divergence debate. We applied Western theories to investigate possible contextual differences in the relationships between learning climate facilitation and turnover intention, and to investigate whether this relationship is mediated by employability, and whether dark leadership is a possible moderator. Methods To test our hypotheses, we collected data from 368 Dutch and 319 Chinese respondents who participate in an executive master’s program, which was analyzed using PLS-Structural Equation Modeling. Results Employees in the Netherlands and China were found to interpret our study variables differently. Separate analyses revealed that, in both contexts, learning climate facilitation was both directly and indirectly, via the balance dimension of employability, negatively related to turnover intention. In addition, in the Dutch sample, dark leadership appeared to weaken the relationship between learning climate facilitation and the corporate sense dimension of employability, but the latter did not seem to be a mediator in the relationship with turnover intention. In the Chinese sample, no moderation effects were found. Discussion Our results show that both learning climate facilitation and dark leadership are important factors in the development and retainment of personnel and that particularly focusing on ‘balancing group and individual goals’ is important to retain personnel, regardless of national context. The latter may indicate the need for convergence of HR practices. At the same time, however, the different interpretations of the study’s variables may indicate divergence in the meaning of HR concepts. In the discussion section, we elaborate on the study’s implications for HR-researchers and -practitioners in national and global business contexts.